FAKTOR PENYEBAB RENDAHNYA MOTIVASI BELAJAR SISWA KELAS X DALAM PEMBELAJARAN SOSIOLOGI DI SMA N 4 KOTA SOLOK - FERTI, ELSA BUDI (Pendidikan Sosiologi, 2014)
This research is motivated by the factors causing low student motivation in learning sociologyat SMA N 4 Solok. It is seen from the internal and external factors, the causes of low studentmotivation because it seems there are still many students who spoke when the teacher explains thelesson, and out of the classroom while the students learn and too lazy to do the work set by theteacher and the students prefer to rely on friends in making assignments. The objectives of thisstudy were 1) to describe the factors causing low student motivation in learning sociology class XSMA N 4 Solok and 2) describe the efforts made by teachers to improve students motivation inlearning sociology at SMA N 4 Solok.In this study the authors use Blooms theory of learning that describes the areas to be thefocus in the areas of learning, namely cognitive, affective and area psychomotor area. This studyused a qualitative research, the type used in this research is to develop a descriptive problemsexamined. Determination of informants conducted by purposive sampling technique, while theinformants in this study of 16 people, the authors determined the students and teachers of subjectssociology, vice principal at the high school N 4 Solok. The data collected in this study is primarydata obtained through the data collection methods such as interviews. The unit of analysis of datawhich comprises the step of reduction, data presentation / analysis of data, and drawingconclusions.Based on the results of research conducted showed that: 1) the factors causing low studentmotivation in learning is due to two factors: external internal dam. External factors, namely theschool environment, family environment, and the methods used in teaching the teacher. Whileinternal factors, namely the willingness to learn, study habits / awareness and the ability of thestudent / IQ. 2) The efforts made by teachers to improve students motivation in learningsociology, has been pursued by means of varying the teaching methods and improving discipline.